Katuk Leaf Consumption with Breast Milk Production in Primipara Breastfeeding Mothers in Pekanbaru - Rika Andriyani; Cecen Suci Hakameri (Science Midwifery, 2022)
The success of breastfeeding is influenced by the production of breast milk from the mother. Lack of milk production results in the failure of exclusive breastfeeding. Breast milk is the single most important food and has many benefits for babies 0-6 months. Katuk leaf is one of the plants that can help increase the production of breast milk. This study aims to determine the consumption of katuk leaves on the milk production of primiparous nursing mothers. This research method is quantitative with a correlational research design using a cross sectional study approach. The number of samples was 35 breastfeeding mothers. Sampling used a random sampling technique with consecutive random sampling. The results of the study obtained a p value of 0.001 and the analysis of the close relationship between the two variables obtained OR (odds ratio) = 15,000. The conclusion is that there is a significant relationship between consumption of katuk leaves and breast milk production in primiparous breastfeeding mothers in Pekanbaru city. So it is hoped that katuk leaves can be used as the main menu in determining the menu when the mother is in postpartum care.